Frequent use of chemical household products is associated with persistent wheezing in pre-school age children. Issue 1 (23rd December 2004) - Sherriff, A; Farrow, A; Golding, J; Henderson, J
Abstract : Background: In the UK and other developed countries the prevalence of asthma symptoms has increased in recent years. This is likely to be the result of increased exposure to environmental factors. A study was undertaken to investigate the association between maternal use of chemical based products in the prenatal period and patterns of wheeze in early childhood. Methods: In the population based Avon Longitudinal Study of Parents and Children (ALSPAC), the frequency of use of 11 chemical based domestic products was determined from questionnaires completed by women during pregnancy and a total chemical burden (TCB) score was derived. Four mutually exclusive wheezing patterns were defined for the period from birth to 42 months based on parental questionnaire responses (never wheezed, transient early wheeze, persistent wheeze, and late onset wheeze). Multinomial logistic regression models were used to assess the relationship between these wheezing outcomes and TCB exposure while accounting for numerous potential confounding variables. Complete data for analysis was available for 7019 of 13 971 (50%) children. Results: The mean (SD) TCB score was 9.4 (4.1), range 0–30. Increased use of domestic chemical based products was associated with persistent wheezing during early childhood (adjusted odds ratio (OR) per unit increase of TCB 1.06 (95% confidence interval (CI) 1.03 to 1.09)) but not with transient early wheeze or late onset wheeze. Children whose mothers had high TCB scores (>90th centile) were more than twice as likely to wheeze persistently throughout early childhood than children whose mothers had a low TCB score (<10th centile) (adjusted OR 2.3 (95% CI 1.2 to 4.4)). Conclusion: These findings suggest that frequent use of chemical based products in the prenatal period is associated with persistent wheezing in young children. Follow up of this cohort is underway to determine whether TCB is associated with wheezing, asthma, and atopy at later stages in childhood.